Identification, Isolation and Determination of Biomarkers for Quality Control of Bush Tea (Athrixia phyllicoides) - Lerotholi, Lefa J.; Chaudhary, Sushil K.; Chen, Weiyang; Veale, Clinton G. L.; Combrinck, Sandra; Viljoen, Alvaro M. (Planta Medica, 2018)
Athrixia phylicoides, known as “bush tea”, grows abundantly in South Africa. An infusion of the leaves is used as a beverage and to treat a multitude of health conditions. The aim of this study was to investigate the chemical variation within A. phylicoides and to identify characteristic compounds for quality control. Samples from 12 locations in South Africa were analysed using ultra-performance liquid chromatography. Hierarchical cluster analysis of the aligned ultra-performance liquid chromatography-time-of-flight mass spectrometry data indicated two groups on the resulting dendrogram, representing 48 samples. Five marker compounds, identified through visual inspection and the construction of a discriminant analysis model, were evident on the ultra-performance liquid chromatography-MS profiles. Four of these compounds were isolated and identified, three as hydroxy methoxyflavones and the fourth as a coumarate, using nuclear magnetic resonance spectroscopy. An ultra-performance liquid chromatography-photodiode array method was developed and validated for the determination of the marker compounds using the isolates as standards. The limits of detection for the four compounds ranged from 0.92 – 2.50 µg/mL. Their recoveries at three concentration levels (1.00, 10.0, and 100 µg/mL) were between 97.0 and 101%, while acceptable intra- and inter-day precision was obtained as reflected by percentage relative standard deviation values below 2.24%. The concentrations of all the marker compounds were found to be higher in samples corresponding to Group 1 of the dendrogram than in those from Group 2. This may be attributable to differences in altitude, climate, and some edaphic factors. Identification of these marker compounds will make a valuable contribution towards the quality control and sustainable commercialisation of bush tea.
Keywords: Athrixia phylicoides; Asteraceae; chemometrics; UPLC; NMR; quality control